The Gaps Between the Self and Professional Evaluation in Mental Health Assessment of COVID-19 Cluster Cases - Liu, Ligai; Wang, Xin; Hao, Yiwei; Yang, Jingming; Yang, Di; Duan, Xuefei; Fang, Gaoli; Han, Bing; Jiang, Chunguo; Li, Junnan; Liu, Yao; Wang, Yang; et al. (Frontiers in Psychology, 2021)
Objective To analyze the discrepancy between self-rating and professional evaluation of mental health status in COVID-19 cluster cases. Method A total of 65 COVID-19 cluster cases admitted to Beijing Ditan Hospital Capital Medical University from June 14th 2020 to June 16th 2020 were included. The patients’ demographic data were collected, and self-rating and professional evaluation of mental health status were completed. The Gaps between self-rating and professional evaluation in different demographic characteristics were compared, and factors correlated with the Gaps are analyzed. Results The results of self-rating were inconsistent with those of professional evaluation. The Gaps of the two dimensions in anxiety had remarkable statistics differences based on participants’ sex, monthly income, anxiety/depression medical history, and infection way. Those suggested that the patients of male, 10000-20000 monthly income, having history of anxiety or depression, and infected from direct contact ways had higher self-rating in relative dimensions. In terms of depression, the subgroups of social insurance type, 10000-20000 monthly income, unmarried, more than nine years of education, more than ten years residing in Beijing, without anxiety/depression medical history, no steady employment, and without physical disease history had higher self-rating in relative dimensions. Conclusion Professional evaluation should be used as the primary evaluation method. Some demographic characteristics may be related to higher self-rating. More researches are needed to determine why certain demographic characteristics are associated with higher self-rating.